Effects of Natural Substance Processed by Penergetic Technology Supplementation in Diet on Growth Performance Carcass Traits and Meat Quality of Finishing Pigs - Phoonsap, Kamolthip; Songserm, Ornprapun; Chumngoen, Wanwisa; Rattanatabtimtong, Sukanya (Journal of Mahanakorn Veterinary Medicine, 2021)
This trial aimed to evaluate the effects of natural substance processed by Penergetic Technology (penergetic-T) supplementation in diets on growth performance and carcass traits in finishing pigs. A total of 150 Duroc x Large White x Landrace pigs at 20 weeks of age were divided into 3 groups. Each group consisted of 10 replications with 5 pigs per replication. The pigs were randomly fed one of three experimental diets as following, control diet: commercial feed (T1), control diet supplemented with penergetic-T 200 ppm (T2) and control diet supplemented with penergetic-T 400 ppm (T3). The experiment was assigned in Randomized Complete Block Design (RCBD). The results showed no significant differences of growth performance among groups (P>0.05). The results of carcass traits showed that pigs fed diet supplemented with penergetic-T 400 ppm had lower Lenden-Speck-Quotient (LSQ) compared to pigs fed diet supplemented with penergetic-T 200 ppm and pigs fed control diet (0.19, 0.20 and 0.23, respectively) (P<0.05). The values of cooking loss of pork from pigs in the groups of the dietary penergetic-T supplementation were lower than those of pork from pigs in the control group (P<0.05), and shear force values of pork from pigs in the groups supplemented with natural feed additive tended to be lower than those from pigs in control group (P = 0.072). Therefore, supplementation of natural substance processed by penergetic technology (penergetic-T) in finishing pig diet has potential to improve carcass traits and meat quality.